TOMASZ Z AKWINU A TEISTYCZNY EWOLUCJONIZM - Chaberek, Michał (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
“Thomas Aquinas and Theistic Evolution” is an article about the problem of using Aquinas’ thought to defend theistic evolution within the Christian theological tradition. The paper begins with definitions of terms such as “evolution” and “species.” The main part of the paper is structured according to the medieval articles written by Aquinas himself, such as those contained in his Summa Theologiae. First, the author presents twelve arguments that can be found in the writings of contemporary Thomists in favor of theistic evolution. In the next part, the author elaborates upon the answer to the question and he goes on to respond to the twelve arguments by referring to Aquinas’ writings. In the conclusion, the author shows seven points of disharmony between the three types of evolution (namely, atheistic, materialistic and theistic) and Aquinas’ teaching on the origin of species.